Role of glutamine synthetase adenylylation in the self-protection of Pseudomonas syringae subsp. "tabaci" from its toxin, tabtoxinine-beta-lactam. - Knight, T J (1986)
Selected pathovars of Pseudomonas syringae produce an extracellular phytotoxin, tabtoxinine-beta-lactam, that irreversibly inhibits its known physiological target, glutamine synthetase (GS). Pseudomonas syringae subsp. "tabaci" retains significant amounts of glutamine synthetase activity during toxin production in culture. As part of our investigation of the self-protection mechanism(s) used by these pathovars, we have determined that GS becomes adenylylated after toxin production is initiated and that the serine released from the zinc-activated hydrolysis of tabtoxin is a factor in the initiation of this adenylylation. The adenylylation state of this GS was estimated to range from E5.0-7.5. The irreversible inactivation by tabtoxinine-beta-lactam of unadenylylated and adenylylated glutamine synthetase purified from P. syringae subsp. "tabaci" was investigated. Adenylylated GS was inactivated by tabtoxinine-beta-lactam at a slower rate than was unadenylylated enzyme. Adenylylated GS (E7.5-10.5) was significantly protected from this inactivation in the presence of the enzyme effectors, AMP, Ala, Gly, His, and Ser. Thus, the combination of the adenylylation of GS after toxin production is initiated and the presence of the enzyme effectors in vivo could provide part of the self-protection mechanism used by subsp. "tabaci".